Poly(N-isopropylacrylamide)–clay based hydrogels controlled by the initiating conditions: evolution of structure and gel formation. Issue 48 (2nd October 2015) - Strachota, Beata; Matějka, Libor; Zhigunov, Alexander; Konefał, Rafał; Spěváček, Jiří; Dybal, Jiří; Puffr, Rudolf
Abstract : The formation of the hydrogel poly( N -isopropylacrylamide)–clay (LAPONITE®) by redox polymerization was investigated, and the main factors governing the gel build-up were determined. Abstract : The formation of the hydrogel poly( N -isopropylacrylamide)–clay (LAPONITE®) by redox polymerization was investigated, and the main factors governing the gel build-up were determined. The significant effect of the redox initiating system ammonium peroxodisulfate (APS) and tetramethylethylenediamine (TEMED) on gel formation and structure was established, making it possible to control the structure of the gel. Moreover, the pre-reaction stage involving the quality of the clay exfoliation in an aqueous suspension and the interaction of reaction components with the clay play a role in controlling the polymerization and gel structure. The molecular and phase structure evolution during polymerization was followed in situ by the following independent techniques: Fourier transform infrared spectroscopy (FTIR), chemorheology, small-angle X-ray scattering (SAXS) and ultraviolet-visible spectroscopy (UV/Vis). The combination of these methods enabled us to describe in detail particular progress stages during the gel formation and determine the correlation of the corresponding processes on a time and conversion scale. The mechanism of gel formation was refined based on these experimental results.